2017
DOI: 10.17265/2162-5263/2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Technologies for Mining Wastewater Treatment

Abstract: Abstract:The mining industry has contributed tremendously to the global economy. However, waste generated by this activity poses many challenges. Current low-cost technologies for the removal of heavy metals from mining wastewater include biosorption, adsorption, CWs (Constructed Wetlands) and waste stabilization ponds. This chapter focuses on sustainable mining wastewater treatment technologies with emphasis on gold mining wastewater. It discusses the technical and environmental challenges associated with min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 77 publications
(101 reference statements)
1
9
0
Order By: Relevance
“…This study demonstrated high removals for Cd and other metals in the pilot-scale CWs, especially in that planted with cattails (CW-B), from the NMD of A-Mine (Figures 3 and 4). The HRT of CWs for mine drainage treatment is typically a few days to several weeks [3,5]. However, in this study, HRT of 1.25 days was sufficient for Cd removal from the NMD without severe clogging.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This study demonstrated high removals for Cd and other metals in the pilot-scale CWs, especially in that planted with cattails (CW-B), from the NMD of A-Mine (Figures 3 and 4). The HRT of CWs for mine drainage treatment is typically a few days to several weeks [3,5]. However, in this study, HRT of 1.25 days was sufficient for Cd removal from the NMD without severe clogging.…”
Section: Discussionmentioning
confidence: 68%
“…Among them, approximately 80 mines with absent owners must treat mine drainage continuously despite a lack of production, which has imposed large economic burdens on national and local governments for over a hundred years [2]. A promising alternative as a passive technology for mine drainage treatment is constructed wetlands (CWs) because of their simple operation, low cost, and moderate effectiveness [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Many ores, mining precious metals, such as gold (Au), copper (Cu), 10 arsenic (As), mercury (Hg), cyanide, and uranium (U), contain high amounts of the poisonous metalloid ions. 11–13 For example, arsenic in most cases comes from mine exploitation, as well as excavating, and regularly has connections to treasured minerals, including sphalerite, pyrite, and chalcopyrite. 14 Arsenic generally dissolves during manufacture and then seeps into groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…Constructed wetlands (CWs) have been recognized as a potential green technology for mine drainage treatment. In fact, they have gained great attention worldwide because of their effectiveness, low cost, simple maintenance, and high biodiversity value [8][9][10]. The substrate serves an important role in heavy metal removal in CWs [10,11].…”
Section: Introductionmentioning
confidence: 99%